ANALISIS KORELASI ANTARA SUDUT SIMPANGAN DAN WAKTU RATAAN PADA BANDUL FISIS DENGAN LATIN SQUARE DESIGN - Putri, Adellia Purnomo; Sofro, A’yunin (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This study aims to examine the relationship between the angle of deviation and the average time length of a physical pendulum. This study uses primary data, namely practicum report data in a physics laboratory. Data collection was conducted under closed conditions with control variables (shaft length, number of oscillations, and radius of gyration) and dependent variables (angle of deviation and average time). The analysis technique used is a statistical approach technique, namely Latin Square Design analysis. The findings of this study indicate that the variables of deviation angle and average time on the physical pendulum have a strong and unidirectional correlation relationship. This result is evident from the value of F0 > Fcritical and the value of Pr (> P) > 0, 05(significant level) where both of these prove that there is a strong reason to reject H0 which means that there is at least 1 difference in the effect of the angle of deviation on the average time. It shows that the angle of deviation affects the average time of the physical pendulum